Features of the pathogenesis, diagnosis, and treatment of panic attacks in young people - M. L. Chukhlovina (Неврология, нейропсихиатрия, психосоматика, 2020)
Objective: to investigate the features of the pathogenesis, diagnosis, and treatment of panic attacks (PAs) in young people.Patients and methods. A total of 39 outpatients (27 females and 12 males) aged 19 to 38 years with PAs were examined. The Panic Disorder Severity Scale (PDSS) was used to measure the severity of clinical manifestations of PAs; the Covey Anxiety Scale was employed to identify an anxiety state. In order to exclude depressed patients from being examined, the Montgomery—Аsberg rating scale was applied to assess the severity of depression. All the patients were divided into two groups: 1) 22 patients with PAs who received standard therapy and the alpha-adrenoblocker proroxan (Vegetrox) as a 15-mg tablet thrice daily for 8 weeks; 2) 17 patients who were prescribed only standard therapy. The patients were examined twice before and 4 weeks after the end of an 8-week vegetrox therapy cycle.Results and discussion. In the patients of both groups with PAs, the total score ranged from 3 to 11, with the median PDSS score of 7. According to the Covey anxiety scale, an anxiety state developed in 33 patients; only the symptoms of anxiety were detected in 6. There was a direct significant correlation between the PDSS and Covey anxiety scale values; Spearman's rank correlation coefficient was 0.681 (p<0.01). The PA severity indexes proved to be significantly lower after incorporating Vegetrox into the standard therapy. Comparing the anxiety scale values in the patients of Groups 1 and 2 after the treatment cycle revealed a significant decrease in the level of anxiety in the patients receiving standard therapy and Vegetrox. This effect of the latter may be explained by the fact that it blocks postsynaptic α1-adrenoceptors and presynaptic α2-adrenoceptors and decreases the stimulation intensity of the hypothalamic structures that are closely connected with the limbicoreticular system.Conclusion. The severity of PAs in young people depends on the level of anxiety. Vegetrox has a significant positive effect on the values of PDSS and the Covey anxiety scale in PAs.